Pendaftaran Tanah Wakaf Menurut PP No. 42 Tahun 2006 - Azhar Azhar (Fakultas Syariah IAIN Laa Roiba Bogor, 2019)
This study aims to analyze the registration of waqf land according to Government Regulation No. 42 of 2006 in Hinai Langkat District, North Sumatra. The method used in this study is a qualitative method by using an empirical, sociological, respondent and interview approach. People in Hinai District consider waqf registration not so important in order to maintain the waqf land. This is due to the fact that people are still used to donating land verbally on the basis of mutual trust in a certain person or institution, the habit of viewing waqf as a pious deed that has noble value in the presence of God without having to go through administrative procedures, and waqf property is considered to belong to Allah alone. will not dare to interfere without the permission of Allah SWT. People also find it difficult to register their waqf land. They have not had the procedure for registering waqf and the problem of service for local KUA employees. The government is seen as contributing because of the lack of socialization of waqf regulations in Indonesia. Keywords: waqf registration, regulation and socialization